A forensic taphonomic study into the differential decomposition rates and patterns of bodies subjected to varying degrees of burns - Keyes, Craig Adam (My University, 2016)
Despite the high number of worldwide fatal burn cases investigated by forensic experts, there is a lack of literature on the effects of burning on soft tissue decomposition. The objectives of this study tested the reliability of the charred body scale (CBS), developed a TBS scoring system for specific burn levels, compared burned and unburned body decomposition rates and patterns, compared summer and winter decomposition rates, and determined if body region or CGS level effects individual body region decomposition. Six Sus scrofa domesticus carcasses were burned to different Crow-Glassman Scale (CGS) levels and left to decompose - two in winter (control, CGS level 2) and four in summer (unburned control, CGS level 1, CGS level 2, CGS level 3). Decomposition patterns, charred body scale (CBS) scores and unique burn level scores were recorded at 50 accumulated degree-days (ADD) intervals. A unique TBS method was developed for each CGS level. This study established that the CBS system is not a reliable method for scoring burned remains. Burning alters normal decomposition processes, including the abnormal bloating of the CGS level 1 pig and the absence of visible bloat in all CGS level 2 pigs. All CGS level pigs exhibited abnormal decomposition patterns. There is a significant difference (p=0.0002) in the decomposition rates of burned remains. The CGS level 1 pig decomposed furthest followed by the CGS level 3 pig, then CGS level 2 pig and finally the unburned control pig. Burning results in the earlier onset of decomposition stages in summer but significantly slows the decomposition rate in winter (p<0.0001). There is a significant interaction between CGS level and body region on the decomposition rate in winter (p<0.0001) and summer (p=0.0228). This research is novel in South Africa and internationally. These preliminary findings will assist forensic experts to better understand the context of burn cases and therefore postmortem events can be more accurately reconstructed.
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree: MSc(Med) in Forensic Medicine Division of Forensic Medicine and Pathology, School of Clinical Medicine, Faculty of Health Science, University of the Witwatersrand, Johannesburg, South Africa 2016